Legislation on the Development of Tourist Villages in the Sociopolitical Scope - Al Anshori, Hannif Andy; Dzulkifli, Muhammad (Ann Publisher, 2025)
Background. The development of tourism villages is a crucial strategy for promoting sustainable community-based tourism in Indonesia. Sleman Regency is an area with significant growth in tourism villages but still faces challenges in resilience, sustainability, and adherence to the principles of community-based tourism. Purpose. This study aims to examine the legislative framework and assessment indicators in the classification of tourism villages in Sleman Regency from a sociopolitical perspective and tourism sustainability. Method. The method used is a qualitative-descriptive approach, combined with relevant policy and regulatory analysis, and the mapping of tourism village assessment indicators sourced from regional regulations, national standards, and international standards for sustainable tourism. Conclusion. The results of the study show that the Sleman tourism village classification system has adopted the principle of sustainability through institutional indicators, community empowerment, environmental and cultural preservation, risk mitigation, and local economic utilization. However, implementing these indicators still faces challenges in terms of consistency, human resource capacity, and village readiness to withstand external pressures such as disasters and climate change. Implementation. This research emphasizes the importance of strengthening operational legislation and periodic evaluation as strategic instruments for ensuring the sustainability and competitiveness of tourism villages.